Preliminary Screening Results Outside the 1945–1965 Birth Cohort: A Forgotten Population for Hepatitis C?. (10th April 2019) - Winetsky, Daniel; Zucker, Jason; Slowikowski, Jacek; Scherer, Matthew; Verna, Elizabeth C; Gordon, Peter
Abstract: In December 2017, our academic medical center implemented universal hepatitis C virus screening among adult hospitalized patients. We reviewed charts of patients screening positive outside the birth cohort (1945–1965) in the first 6 months after implementation. Documented risk factors were common in younger patients but rare in patients born before 1945.